Summertime: fiction - Coetzee, J. M. (Viking Penguin, 2009)
In this autobiographical novel, a young English biographer is researching a book about the late South African writer John Coetzee, focusing on Coetzee in his thirties, at a time when he was living in a rundown cottage in the Cape Town suburbs with his widowed father--a time, the biographer is convinced, when Coetzee was finding himself as a writer.